2013
DOI: 10.1007/s10903-013-9902-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Interventions for Arabic Women: A Literature Review

Abstract: Similar to other Middle Eastern countries, breast cancer is the most common cancer among women in Qatar with increasing incidence and mortality rates. High mortality rates of breast cancer in the Middle Eastern countries are primarily due to delayed diagnosis of the disease. Thus screening and early detection of breast cancer are important in reducing cancer morbidity and mortality. With the aim of updating knowledge on existing interventions and developing effective intervention programs to promote breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
5
39
0
Order By: Relevance
“…Furthermore, difficulties in promoting education related to BSE have been cited 15, with approximately 3% 22 to 24% of women administering a BSE 21, 23 and 12.5% undergoing a CBE 15.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, difficulties in promoting education related to BSE have been cited 15, with approximately 3% 22 to 24% of women administering a BSE 21, 23 and 12.5% undergoing a CBE 15.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, another comprehensive literature review exploring what has been reported as effective interventions in increasing breast cancer screening uptake in Arab populations was conducted ( Figure 2). 15 Table 1 presents intervention overview of included studies.…”
Section: Studies Included In Results (N=81)mentioning
confidence: 99%
“…18,19,20,21 However, Arab women currently face a significant risk of high mortality rate from breast cancer due to frequent diagnosis in the advanced stages of the disease. 22,23,24,25 Drawing on the findings of our recent study in Qatar 11,13,14 and a comprehensive literature review of studies, 10,15 we recommend several categories of intervention strategies to promote early detection of breast cancer among Arab populations. To effectively decrease breast cancer mortality rates for Arab women, it is imperative that health care professionals employ multilevel interventions and maximize the synergic effect between each level of intervention.…”
Section: Recommendations To Health Care Professionalsmentioning
confidence: 99%
“…Several studies have found that culturally-sensitive breast cancer education programmes can have a significant impact on changing knowledge and beliefs about breast cancer (Hall et al, 2005;Bickell et al, 2009). Researchers have recently been focusing on the possibility that culturally-tailored behavioural change programmes may affect cancer screening practices to better eliminate known barriers and provide appropriate interventions (Simon, 2006;Donnelly and Hwang, 2015). Little is known about the perceptions, attitudes, barriers and facilitators related to breast cancer prevention perceived by Omani women.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as health beliefs and attitudes towards breast cancer, general breast cancer knowledge and screening knowledge, socioeconomic status and level of education have also been linked with screening use (Raza et al, 2012;Donnelly and Hwang, 2015).…”
Section: Introductionmentioning
confidence: 99%